Uma proposta de API para desenvolvimento de aplicações multiusuário e multidispositivo para TV Digital utilizando o Middleware Ginga - Silva, Lincoln David Nery e (2008)
The Interactive Digital TV applications progress does not occur at the same speed we found at Web or Desktop applications. This fact is due to constraints encountered in both hardware and the middleware in which applications run, and also due to the limited way we have to interact with the TV: with the traditional remote control. In the Brazilian scene, the middleware Ginga specification allows the incorporation of new functionalities through the Device Integration API, which is target of this dissertation. The API allows TVDI applications to use mobile devices both as a means of interaction, and to share its multimedia resources. As a result of the API use, TVDI applications are able to employ new possibilities not available in others existing Digital TV middlewares, like the use of multimedia resources and multiuser support. The new API has been implemented and applied to develop TVDI applications aiming to explore the new advanced features available.